Proposta e implementação de sistema para caracterização eletromecânica estática e dinâmica de motores rotativo e linear de relutância chaveada - Oliveira, Danilo Nobre (2008)
The main objectives of this work are the proposition and implementation of a system for the static and dynamic characterization of low power rotary and linear switched reluctance machines. Through the static and dynamic characterization of those machines, mathematical models are developed for both machines, which allow the development of the simulation of the machine integrated with its control system. Futhermore, the models also allow the verification of design values, as well as the possibility of improvement in the machine design methodology – for the rotary and linear switched reluctance machines. The analysis of the electromagnetic static characteristics of both machines was based on simulation (using finite element and the magnetic circuit analysis methods) which was validated by experimental procedures (using three measurement methods), while the analysis of the mechanical static characteristics were carried out only for the rotary machine, involving the simulation and measurement of the mean torque value. The analysis of the dynamic characteristics of both machines was done through the development and implementation of two different electronic drive and control systems (one system for the rotary machine and other for the linear machine), with closed loop control for the position (of the movable part) and hysteresis current control.